The winter house [videorecording (DVD)] - Boynton, Keith; Taylor, Lili; Arnaud, François, 1985-; Fowler, Beth, 1940-; Bradbury, Stephen C.; Emery, Hunter (Freestyle Digital Media, 2023)
Eileen is grieving. She needs to get away. She rents a house in a remote corner of New Hampshire, in the dead of winter, where no one is likely to bother her. But wouldn't you know it? Someone does. Jesse is young, impetuous, charismatic, and evasive. He claims to be the son of the couple who own the house, but Eileen isn't inclined to believe him. She's a brilliant writer with her own demons and secrets; she knows a fellow lost soul when she sees one. As winter wears on in the lonely house at the edge of nowhere, Eileen and Jesse try to offer each other salvation both knowing full well that the opposite is far more likely.